PERAN MGMP ATAU KOMBEL (KOMUNITAS BELAJAR) DALAM MENINGKATKAN KOMPENTENSI PEDAGOGIK GURU DI SD IT AL_'IZZ KABUPATEN SUKABUMI - Asep Rizkiyana; Siti Qomariyah; Ujang Ruslandi; Vikri Dwiki Sukandi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to explore the role of Musyawarah Guru Mata Pelajaran (MGMP) or Kombel (Learning Community) in enhancing the pedagogical competence of teachers at SD IT AL-'IZZ in Sukabumi Regency. MGMP functions as a collaborative forum for teachers to share knowledge, experiences, and best practices in teaching. Through various activities such as training, workshops, and discussions, MGMP is expected to improve teachers' skills and motivation in implementing effective learning processes.The research method employed is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results indicate that active participation of teachers in MGMP positively contributes to the enhancement of their pedagogical competencies, although several challenges exist, such as low member participation and limited resources. Recommendations for improving the effectiveness of MGMP include developing relevant training programs and support from school management. This research is anticipated to provide insights for the professional development of teachers and the improvement of educational quality at SD IT AL-'IZZ.